Yakiv Yatsynevych: New Look at the Periodization of Life Creation - Chamakhud, Daryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of research. Reconstruction of life-creation of a little-investigated Ukrainian composer Yakiv Yatsynevych is a troublesome process that demands enormous efforts. The works of T. Filenko, O. Semirozum, L. Korniy, and other researchers do not propose a solution to the problem of periodization. In this regard, it’s necessary not only to continue the studying of bibliographical events, facts and even decennaries of Y. Yatsynevych life, that were ignored by scientists’ focus, including the compositor’s music heritage in different genres, but also to generalize already gained finds of musicologists aside with own elaborations in this monographic theme. Objective of the research is to form the periodization if the artist’s life- creation on the bases of earlier unknown materials from archives in Kyiv, taking into account the external and internal factors. During the fulfillment of the mentioned tasks such methods of investigation were used: source study (search of documents in the archives of Kyiv), systematization (division and classification of founded materials), historical-chronological (streamlining and reconstruction of the compositor’s biographical way), analysis (music works studying), synthesis (joining of gained knowledges), generalization (periodization forming). Scientific novelty consists in the fact that the periodization of Y. Yatsynevych life-creation is formed in the Ukrainian musicology for the first time. Periodization is based on the author’s investigations of bibliographical documents and composer’s music heritage materials in eight volumes in Kyiv archives collected over many years. Research results and perspectives. Taking into consideration biological, chronological, social, psychological and creative age of Y. Yatsynevych, and also artist’s sociocultural, historicalpolitical peculiarities, geographical place of residence, genre diversity of his music, the universal periodization of Y. Yatsynevych life-creation is formed. Early Period, up to 1905 (formation of the basis of composer’s creativeness, relatively uncomplicated music, narrow circle of genres): First Phase, up to 1900 (childhood and youth years in Bila Tserkva, period of study in Kyiv, formation as conductor and composer, Kyiv artistic environment influence, music works are not preserved). Second Phase, 1900–1904 (exercising piano music, active music work in Kyiv). Crisis of Middle Age in Composer’s Art, 1905–1915 (absence of qualitative musical works, conducting activities, non-musical work at public offices). Adult Period, 1915–1930 (complication of music language and genre system, exercising of chamber and amplitudinous forms, the top of composer’s creativity, embraces work in Kyiv and Odessa): First Phase, 1915–1925 (fruitful activity in artistic and church life of Kyiv, collecting of folklore material, choir music domination, repertoire expansion of piano works and instrumental ensembles). Second Phase, 1925–1930 (heading of the artistic life of Odessa, appearing of chambervocal compositions, activation of new art genres: oratorio, opera, symphony, cinema music). Enforced Crisis, 1930–1940 (non-recognition of creativity, difficult social conditions, absolute efficiency to non-music work, creation of single music compositions). Late Period, 1940–1945 (post-crisis condition, pause of silence, deportation to Adyheia АR, decreasing of artistic activity, a little number of music works in big magazines). Suggested periodization depicts the entire picture of Y. Yatsynevych life and creation and is the basis for further investigations of his music heritage.